INHIBITORY EFFECTS OF GREEN TEA EXTRACT ON ADP AND THROMBIN INDUCED PLATELET AGGREGATION - Aiamsa-ard, Tipsuchon; Devakul Na Ayutthaya, Watcharaporn; Phetmanee, Thidarat (Interprofessional Journal of Health Sciences, 2023)
The study was performed to investigate the effects of green tea extract (GTE) on platelet aggregation in Wistar rats. Forty male rats were used in this study and treated with GTE for 35 days. Experimental groups were as follows; control group; distilled water, aspirin 10 mg/kg/day, green tea extract 25, 50 and 100 mg/ kg/day. The platelet aggregation was measured by using microplate reader after inducing platelet aggregation by adenosine diphosphate (ADP) and thrombin. The results showed that green tea extract 25, 50 and 100 mg/kg/day tended to inhibit platelet aggregation induced by ADP and thrombin. However, only green tea 25 mg/kg/day significantly suppressed platelet aggregation when compared with the control group (p<0.05). This experiment showed the potential preventive effects of low dose GTE against platelet aggregation via ADP and thrombin pathway. Thus, green tea extract may be beneficial for preventing against cardiovascular diseases.